Severity of metabolic syndrome unfavorably influences oxidative stress and fatty acid metabolism in men - Zák, Ales; Tvrzická, Eva; Vecka, Marek; Jáchymová, Marie; Duffková, Ladislava; Stanková, Barbora; Vávrová, Lucie; Kodydková, Jana; Zeman, Miroslav (The Tohoku journal of experimental medicine, 2007)
Metabolic syndrome (MS) is defined by the clustering of several components (MSC), which include abdominal fat accumulation, impaired glucose homeostasis, hypertriglyceridemia, lowered high-density lipoprotein cholesterol, increased blood pressure, and hyperuricemia. Metabolic syndrome is also accompanied by increased oxidative stress and inflammation as well as by altered composition of esterified fatty acids (FA). Therefore, we have investigated 210 men (categorized into six groups with increasing number of MSC) to find trends in the extent of oxidative stress, FA pattern and frequency of pathological alleles of the selected candidate genes for lipid metabolism. Increasing number of MSC was connected with the raised serum glucose and insulin, increased concentrations of conjugated dienes in low-density lipoprotein (all p < 0.0001), and high frequency of e2 and e4 alleles of the apolipoprotein E gene (p < 0.005). However, the last significance was lost after the adjustment for age. The incidence of 54Thr allele for intestinal isoform of the fatty acid-binding protein (FABP-2) gene was comparable in all groups. The most important findings were the raised content of saturated FA and the increased activities of Delta9 and Delta6 desaturases (all p < 0.0001), and the decreased content of polyunsaturated FA n-6 family and the decreased activity of Delta5 desaturase (both p < 0.001) in connection with increasing number of MSC. In conclusion, the severity of MS is connected with the progression of oxidative stress and the unfavorable changes in the FA composition. These changes are independent of the studied gene polymorphisms.
Keywords: mastné kyseliny; dieta; Diet; oxidační stres; Metabolic Syndrome; Adult; Male; lidé; dospělí; mužské pohlaví; metabolický syndrom; Oxidative Stress; lidé středního věku; Fatty Acids; Humans; Middle Aged